Accumulation and Release of Arsenic from Cast Iron: Impact of Initial Arsenic and Orthophosphate Concentrations. (15th April 2021) - Tang, Min; Lytle, Darren; Botkins, Jacob
Highlights: Corroding iron scale can continue to accumulate arsenic (As) after 7.5 years. Higher initial As levels led to higher As accumulation rate. Orthophosphate (PO4 ) caused high As release from the iron scale in the short-term. The PO4 displaced a small fraction of total accumulated As in iron scale. Most accumulated PO4 were strongly bound to certain iron scale sites. Abstract: Various iron oxyhydroxide and oxide minerals commonly found in old cast iron pipe scale were shown to exhibit high and similar affinity for arsenate [As(V)] and orthophosphate (PO4 ) via adsorption, co-precipitation, and other factors. PO4 is a common drinking water corrosion inhibitor. This 7.5-year study examined the accumulation and release of As from an old cast iron pipe scale by changing initial As(V) (0, 75, or 180 µg/L as As) and initial PO4 (0 or 3 mg/L as PO4 ) levels in the simulated drinking water. The results showed that sites within the iron scale accumulated As with a large capacity and concentrated 27% of the total amount As in water into the scale during the 7.5-year study. When no PO4 was added, the As accumulation followed a linear regression model with an accumulation rate of 0.27/hr (R 2  = 0.80, p < 0.001), and higher initial As level of 180 µg/L (vs 75 µg/L) resulted in 2.3-3 times larger As accumulation rate at 0.25 mg/day (vs 0.084-0.11 mg/day). As much as 44 µg/L As was released back to water following the changes in the initial As and PO4 concentrations in water. Addition of 3 mg/L PO4 caused a rapid increase in As release from iron scale that gradually dropped off with time while PO4 was incorporated into the scale and most PO4 remained tightly bound to certain iron scale sites. Proactive measures such as sampling for As in the distribution systems following PO4 corrosion control treatment changes would help identify exposure risks. Graphic abstract: Image, graphical abstract